Antimicrobial Activity of Bacopa caroliniana - DULGER, BASARAN; HACIOGLU, NURCIHAN (Asian Journal of Chemistry, 2010)
Ethanolic extract obtained from Bacopa caroliniana (Walt.) B.L.Robins (Scrophulariaceae) was investigated for its antimicrobial activity against Escherichia coli ATCC 11230, Staphylococcus aureus ATCC 6538P, Klebsiella pneumoniae UC57, Pseudomonas aeruginosa ATCC 27853, Proteus vulgaris ATCC 8427, Bacillus cereus ATCC 7064, Mycobacterium smegmatis CCM 2067, Listeria monocytogenes ATCC 15313, Micrococcus luteus CCM 169, Candida albicans ATCC 10231, Rhodotorula rubra DSM 70403, Kluyveromyces fragilis ATCC 8608, Debaryomyces hansenii DSM 70238 and Hanseniaspora guilliermondii DSM 3432 by disc-diffusion method. The extract has strong antimicrobial effects against the tested microorganisms especially the bacterium Staphylococcus aureus and the yeast culture Candida albicans. The findings support the use of this plant in traditional medicine.